SANLÍ BILIMLENDIRIWDE OQÍTÍWShÍNÍŃ ORNÍ HÁM WAZÍYPALARÍ - Orazbaeva, G.U. (SCIENCE and SOCIETY, 2025)
This article provides information about the role and main tasks of teachers in a digital learning environment. Recommendations are made on acquiring the necessary digital competencies to take their place in modern education and develop competitive personnel in the labor market.